The efficiency of Using Attribute and Performance- Based Activity Methods to Raise the Level of Control Deviation A field study in Jaber Bin Hayyan Factory - Aljuboori, Intisar saber; Agha, Nada Abdu-lrazak (Journal of Economics and Administrative Sciences, 2021)
Cost is the essence of any production process for it is one of the requirements for the continuity of activities so as to increase the profitability of the economic unit and to support the competitive situation in the market. Therefore, there should be an overall control to reduce the cost without compromising the product quality; to achieve this, the management should have detailed credible and reliable information about the cost to be measured, collected, understood and to analyze the causes for the spread of deviations and obstacles the management faces, and to search for the factors that trigger the emergence of these deviations and obstacles